Impedance spectroscopy using microscopic reference electrodes to analyze different rate-determining steps in aqueous dye-sensitized solar cells using nitroxide radicals as redox mediators - Holzhacker, Daniel; Ringleb, Andreas; Schlettwein, Derck; Justus Liebig University Giessen (My University, 2024)
For new components in dye-sensitized solar cells (DSSCs), identification and quantification of rate-limiting steps is needed to evaluate their applicability. This is particularly important if fundamental changes are studied. In this work, the use of a micro-reference electrode in DSSCs is proposed to increase the significance of electrochemical impedance spectroscopy. The recombination of charge carriers at the photoanode and the regeneration of redox mediators at the counter electrode, which typically occur on similar timescales, could be studied separately but simultaneously in cells under operating conditions. This is particularly useful in the study of water-based DSSCs. Here, cells with 2,2,6,6-Tetramethylpiperidinoxyl (TEMPO) or 4-Hydroxy-TEMPO (OH-TEMPO) as redox mediators using additives like 1-Methylbenzimidazole (MBI) are discussed. It was revealed that the charge transfer resistance (RCE) for the reduction of the oxidized redox mediator at the counter electrode (CE) limits the fill factor (FF) of such DSSCs. TEMPO/MBI electrolytes yielded low RCE and high FF, whereas OH-TEMPO in otherwise identical cells resulted in large RCE, low FF, and low conversion efficiencies. This indicates that the interface between the CE and the electrolyte significantly influences the DSSC performance of these cells and strongly depends on the electrolyte composition. Important optimization strategies could be discussed based on the present results.
Keywords: ddc:530